Models and Political Attitudes of Fundamentalist Groups in Indonesian Presidential Elections - Ahmad, Jafar; Firmanda, Hengki; Wafi, Mahmud Hibatul (Jurnal Ilmiah Peuradeun, 2023)
Islamic fundamentalist groups played an important role in Indonesia's 2019 presidential election. They openly sided with the number 2 candidate, Prabowo Subianto-Sandiaga Solahudin Uno. Even today, the presidential election was marked by polarization and religious sentiments that are very strong and sharp. This study examined the model of presidential election contestation that will likely take place in 2024, the position of fundamentalist groups in political contestation, and its relation to religious polarization trends. This qualitative research used a case study approach to explore political models and attitudes in presidential election contestation. Interest group theory was placed to analyze the issue. The results showed that the map of contestation that will occur in 2024 will still be the same as the 2019 presidential election contestation. Second, the division between religious groups will still occur in the 2024 presidential election. Third, the alignment of religious fundamentalist groups in the 2024 presidential election will lead to figures willing and able to accommodate their groups.